Redox‐Neutral Aromatization of Cyclic Amines: Mechanistic Insights and Harnessing of Reactive Intermediates for Amine α‐ and β‐C−H Functionalization. Issue 50 (9th November 2016) - Ma, Longle; Paul, Anirudra; Breugst, Martin; Seidel, Daniel
Abstract: Cyclic amines such as pyrrolidine and piperidine are known to undergo condensations with aldehydes to furnish pyrrole and pyridine derivatives, respectively. A combined experimental and computational study provides detailed insights into the mechanism of pyrrole formation. A number of reactive intermediates (e.g., azomethine ylides, conjugated azomethine ylides, enamines) were intercepted, outlining strategies for circumventing aromatization as a valuable pathway for amine C−H functionalization. Abstract : Intermediates wanted : A combined experimental and computational study provides detailed insights into the mechanism of pyrrole formation from pyrrolidine and aromatic aldehydes. A number of reactive intermediates (e.g., azomethine ylides, conjugated azomethine ylides, enamines) were intercepted, outlining strategies for circumventing aromatization as a valuable pathway for amine C−H functionalization.